Upaya Keluarga dalam Mencegah Terjadinya Clubbing Culture - Bonifasia Telaumbanua; Megawati Naibaho; Evimawati Harefa (Journal New Light, 2025)
Clubbing culture is one form of moral decline that is happening in the world today. Most of the victims of this culture are the young generation. The habits of the young generation in clubbing groups are smoking, drinking alcohol, free sex and bisexuality. The development of clubbing culture previously only took place in big cities, but now it has developed massively even in small cities. This thesis is written using the library research method. The researcher collects various data about clubbing culture and analyzes it carefully. Handling clubbing culture needs to involve the role of parents. Parents have an important role to educate and accompany children in the family. The purpose of this writing is to provide new awareness to parents as the first and main educators of children. Parental guidance and assistance to children can prevent children from falling into the world of clubbing. From the results of the study, it was obtained that the family has a very important role in shaping a person's personality and morals. The implication of this research to encourage parents to carry out their obligations to guide children in the family. The most effective parental guidance process is parental affection for children and good life examples.